Brainfluence - Dooley, Roger, 1952- (BookaVivo, 2021)
A book to persuade and influence others " book that concentrates all the news of neuromarketing According to neuroscience, 95% of our thoughts, emotions and learning occur before we are aware of it, however the great efforts of the marketing continue to focus on rational messages that appeal to the 5% Brainfluence explains how the brain works and explains both how its functioning influences our actions and also how it can influence how we think Through 100 brief tips, essential for any expert in marketing or communication, you can learn how to position your products, how to set prices, build brand loyalty and much more. It is also essential reading for all of us who consume daily and let ourselves be influenced by those who make use of these 100 tips.